Análisis financiero en la Empresa “Comercializadora Mena” de la ciudad de Loja, periodos 2020-2021. - Lima Espinoza, Katerine del Rosario (2022)
The thesis work called: Financial analysis in the Company "Comercializadora Mena" of the city of Loja, periods 2020-2021, was carried out as a prerequisite to opt for the degree and Title of Engineer in Accounting and Auditing, Public Accountant - Auditor, thus complying with the current Academic Regime Regulations. The general objective of this study was to carry out a financial analysis in the Mena Trading Company of the city of Loja, periods 2020 - 2021; which facilitated knowing the economic and financial performance of the company to know in detail the behavior of the accounts from one period to another for correct decision making. For the elaboration of the work, the following research methodology was used. The methods used were: scientific, deductive, inductive, analytical, mathematical, synthetic and statistical. Among the applied techniques were: the bibliographic compilation, the observation and the interview with the owner manager of the Marketing Company; all this in order to collect information on the situation of the company and its financial economic status, and thus subsequently the review of the financial statements was carried out to carry out the vertical and horizontal analysis in reference to the balance sheet and the income statement of the years 2020 - 2021, to know the composition of assets, liabilities, equity, and income items, in relation to the changes that occurred from one year to another. Then the financial indicators of liquidity, indebtedness and profitability were applied; to later present the report of the financial analysis of the company under study. In the conclusions it was determined that from the vertical and horizontal analysis it was possible to know the economic situation of the company, as well as the most significant general variations, assets and liabilities increased by 38.62%, equity a variation not relevant of 2.70%; in the income statement a decrease in total income, while expenses showed an increase and sales costs a negative variation, causing with this an alteration in its profit / loss for the year. Next, after applying the financial indicators, it was shown that the company has positive current liquidity, with a current ratio of 1.37% on average, an average level of indebtedness of 75.32%, and an ROE of 31.96.% on average. Finally, a financial analysis report was prepared, consisting of the results, conclusions and recommendations that serve as a guide for the Manager to improve the development of activities in the Mena Marketing Company; in effect, its correct application allowed the identification of errors in its management, and to arrive at the proposal of alternative solutions aimed at correct decision-making.